etermination of Nitrate, Potassium, and Calcium using Ion-Selective Sensors in Soilless Plant Growth Media of Some Vegetables - Melda ALTIKATOĞLU; İbrahim IŞILDAK (Türkiye Tarımsal Araştırmalar Dergisi, 2017)
Since it is important to transfer the minerals desired by plants for a long time in a controlled manner, simple and economical new micro and macro scale agricultural production systems are needed. In this study, the nutrients in the plant nutrient solutionwere kept at the required level according to the needs of the plant, using computer controlled potentiometric micro-sized chemical sensor systems. Polyvinylchloride (PVC) -based ion-selective sensors have been used to sensitively and selectively measure the concentration of macro nutrient NO3−, K+, and Ca2+ions in the hydroponic solution. It has been found that the nitrate, potassium and calcium ion levels required for the green pepper and eggplants grown in the greenhouse are different. The results showed that in the first two months of growth, the pepper consumed nitrate in a lesser amount than the eggplant. In addition, it was determined that the amount of potassium consumed by plants was higher than that of other nutrients.